Building Information Modelling for Project Cost Estimation - Aman, Muhammad Syaiful Aliff; Azeanita Suratkon, (Recent Trends in Civil Engineering and Built Environment, 2021)
Building Information Modelling (BIM) is known as n-D modelling can be defined as a collaborative platform to process, produce, communicate and analyze the construction projects using a digital information model throughout the project construction life-cycle. BIM 5D focuses on cost modelling and cost calculation. This study aims to identify the benefits, challenges, and issues during BIM implementation for project cost estimation (BIM 5D) performance among the industry players. A solution to reduce issues and challenges will also be investigated in this research. Data acquisition was made through an online questionnaire platform as research instruments, namely ‘google Form’, were used for this quantitative study and distributed to the respondents. Data analysis was done using Statistical Package for Social Science Windows 25 (SPSS) and expressed in frequency, percentage, and mean for items related to BIM benefits, challenges, issues, and solutions. In order to achieve objective one and two, frequencies were used to identify the benefit, challenges, and arise issues in using BIM 5D that industry player experience. Meanwhile, Mean ranking analysis was used to determine which type of result has the most choice among the industry players. It was found that BIM 5D in providing a better graphical representation of building models and helping the quantity project team understand the project view was most beneficial with a mean of 4.16. Next, the finding found that BIM 5D software could slow down computer processing speeds and lack of BIM trained professional become a significant issue and challenges for the industry with the mean 3.92 and 4.26 respectively. All the recommendation from industry experts would also be collected for uses by the upcoming researcher to improve BIM 5D so that the technology could achieve better performance.